ANALISIS TATO, NPM, DAN ROA TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN FOOD & BEVERAGE - Sulistyowati, Sulistyowati; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to test the influence of total assets turnover (TATO), net profit margin (NPM), andreturn on Assets (ROA) to the profit growth of go public companies. The research sample has been conductedby using purposive sampling. There are 50 financial statementswhich have met the criteria have been obtainedfrom 10 food & Beverages Companies in 2010-2014 periods.The data analysis has been done by usingmultiple regressions analysis and the independent variables i.e.: total assets turnover (TATO), net profitmargin (NPM), and return on assets (ROA). The dependent variable is profit growth (PL). The results of thisresearch have found that the variables i.e.: total asset turnover (TATO), net profit margin (NPM), return onAssets (ROA) have significant influence to the profit growth (PL). This finding is supported by the coefficientdetermination (R2) is 0.799 which shows that 79.9% of the profit growth can be explained by the variables i.e.:total assets turnover (TATO), net profit margin (NPM), and return on Assets (ROA). Meanwhile, theremaining is 20.1% has been influenced by other variables which are not included in the research models.